PENGARUH TEKNIK CERITA BERANTAI TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK KELAS IV SD NEGERI 23 AMPENAN TAHUN PELAJARAN 2019/2020 - Safitri, Asni; Safruddin, Safruddin; Setiawan, Heri; Hakim, Mansur (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2023)
This research purpose to comparison the effect of the chain story technique on the speaking skill of 4th grade students at elementary school 23 Ampenan. This research is an quasi experimental type nonequivalent control group design. The population in this research were all 4th grade students in elementary school 23 Ampenan. The sampling technique used was saturation sample. The data of this research were collected by using observation, speaking skill test with assessment rubric and documentation. The data from students’ speaking skill test in the form of pretest dan posttest, then its tested for normality by the kolmogorov-smirnov test and then its also tested for homogeneity using the varian anylisis test (test of F). The test result showed that the data were normally distributed and homogeneous. Then, the data were analyzed using independent t test. Where the value of tcount = 3.304 > ttabel = 2.010, which means that Ha wad accapted and Ho was rejected. This is shows that there was an influence of the chain story technique on the speaking skill of 4th grade students at elementary school 23 Ampenan.